Analisis Potensi Ternak Kambing di Kabupaten Lombok Barat - I Nyoman Ciptayasa; Muhamad Yasin; Hermansyah Hermansyah (Faculty of Animal Husbandry, University of Mataram, 2016)
This study aimed to analyze the sub-district basis goat development in West Lombok Regency, West NusaTenggara Province; identify development strategies of goat; as well as identify potential goat as the leadingcommodity in West Lombok. The research method is a survey and analysis of secondary data. Data analysiswas using with Location Quotient (LQ), Shift Share Analysis, Overlay Analysis and SWOT Analysis. Theresults showed by LQ analysis, there are four districts which are the basis of goats in West Lombok District isSekotong, Lembar, Gunungsari and Batu Layar. Value analysis LQ goats in the district is above 1. Regionsare encouraged to be a coating region goat development in West Lombok is Labuapi and Kediri. District ofless advisable become basis for the development of goat is Gerung, Kuripan, Narmada and District Lingsar.Based on the results of SWOT analysis, goat farming in West Lombok district tend to experience slowergrowth from year to year.